Allocation of IPTV streams over broadband wireless through fuzzy logic control - Razavi, R.; Fleury, M.; Ghanbari, M.; Sammak, H. (2009 IEEE Symposium on Computers and Communications, 2009)
IPTV video services are under development for broadband networks, with final hop delivery across a wireless link. Within these networks, dedicated subchannels transport different types of traffic (video, voice, data...). This paper proposes fuzzy logic control (FLC) to allocate video streams within an IPTV subchannel subject to fluctuating available bandwidth. The method employs spatial and temporal complexity metrics to judge the appropriate share of available bandwidth, taking account of genre and dynamic coding rate fluctuations. So that the video sources can adjust their rates to the likely available bandwidth across the wireless link, reliable prediction of available bandwidth over time is also proposed. In tests, the FLC, which serves to merge the spatial and temporal metrics into a single control output, results in an overall gain in video quality over static equal allocation of bandwidth and also compensates streams that would otherwise suffer from an inadequate or alternatively an unnecessarily large bandwidth share.